Investigations on the origin of ferromagnetism of Cu doped anatase TiO2 nanotubes. (February 2017) - Zhou, Zhongpo; Wang, Haiying; Zou, Zhaorui; Du, Meng; Guo, Jingjing; Yang, Zongxian
Graphical abstract: Highlights: Undoped, N-doped, Cu-doped and Cu/N-codoped TiO2 are fabricated by anodization. Structure, morphology, optical, electronic and magnetic properties are studied. Cu Doping generates numbers of VO s in TiO2 ; N doping decreases the VO s density. Saturation magnetizations of samples are in consistent with the DFT calculations. Ferromagnetic behavior is explained by the BMP theory involving VO s. Abstract: The role of oxygen defects and dopants of Cu and N on ferromagnetism is discussed in undoped, N-doped, Cu-doped and Cu/N-codoped anatase TiO2 nanotube-arrays fabricated by two-step anodization method. X-ray photoelectron spectroscopy shows the presence of Cu 2+ and/or Cu + in the distorted octahedral coordination of TiO2 . The UV–vis absorption spectra and photoluminescence spectra reveal the presence of oxygen defect related the peaks of absorption and emission in Cu-doped and Cu/N codoped-TiO2 . Room temperature ferromagnetism is observed in all the TiO2 nanotubes. The saturation magnetizations for those specimens decreases in the order of Cu-doped, undoped, Cu/N-codoped and N-doped samples, which are in consistent with the results of the first-principles calculations based on density-functional theory. It is speculated that both oxygen vacancies and Cu d -states are involved in the ferromagnetism. Spin polarization occurs by the formation of bound magnetic polaron between electrons in Cu + /Cu 2+ d-states and the unpaired spins in oxygen vacancies.